A nephrological perspective of herbal remedies on the progression of chronic kidney disease: A systematic review - Mohammad M. AlAhmad, Yamama Al Namer, Subish Palaian, Muaed Jamal Alomar (Journal of Applied Pharmaceutical Science, 2024)
Medicinal herbs are currently making a comeback as they appear to offer advantages over pharmaceuticals in combating chronic kidney disease progression. Conclusive evidence of their safety and efficacy is lacking. Therefore, this unfunded review was conducted to provide a more detailed picture of this issue, serving as a fruitful addition to the literature pool concerned with phytochemicals safety and efficacy in this disease. A systematic approach using specific search terms was used to find 49 articles meeting the study’s inclusion criteria after the study authors scrutinized the articles from different perspectives independently. Many plants were able to delay disease progression by lowering blood pressure via suppression of the renin-angiotensin system, antioxidant and anti-inflammatory effects, and increasing nitric oxide levels; lowering blood glucose levels; improving lipid profile via lipid resistance and oxidation induction; lowering proteinuria; and lowering serum uric acid levels as uricostatic or uricosuric agents, or both. In contrast, some herbal preparations increased blood pressure, induced insulin resistance, and promoted uric acid production through their adrenergic components or mineralocorticoid-like effects. In conclusion, based on the validity of the results obtained, recommendations were made for the proper use of herbal medicines in patients with vulnerable kidneys and for future research directions.
Keywords: Blood glucose, blood pressure, chronic kidney disease, dyslipidemia, herbal medicine, hyperuricemia